Differences in dentofacial characteristics between southern versus northern Chinese adolescents - Gu Yan; Hagg Urban; Wu John; Yeung Shadow (Sciendo, 2011)
Aim: To compare the dentofacial characteristics of southern and northern Chinese adolescents.